EXTREMELY ATTRACTIVE NEW MATERIAL TYPE (CARBON FOAM) MADE FROM RECYCLED WOOD BIOMASS USING THE MICROWAVE IRRADIATION HEATING DURING THE CARBONIZATION STAGE - Lucian Paunescu; Eniko Volceanov; Adriana Ioana; Bogdan Valentin Paunescu (Nonconventional Technologies Review, 2022)
Carbon foam, an extremely attractive new material type for important fields of application, with low density (0.28 g cm-3), low thermal conductivity (0.110 W m-1 K-1), relatively high compressive strength (3.5 MPa), high electrical conductivity (29.8 S m-1), and very high electromagnetic shielding effectiveness (46 dB) was experimentally made using recycled wood biomass from industrial wood processing and aqueous solution of sucrose. The carbonization was performed by heating at 750 ºC through microwave irradiation technique, the pressed and dried material in the intermediate state being introduced into a SiC crucible with a lid, thermally protected with ceramic fiber, without inert medium. The specific energy consumption was very low (0.785 kWh/kg), unlike the high energy consumption of the usually carbonization stages. The optimal carbon foam specimen was considered suitable for the special application fields (military, aeronautics, construction, transport).